Climatic Niche Modelling Reveals Limited Phylogenetic Niche Conservatism in New World Crocodylians - Andrés L. Rodriguez‐Cordero; Nancy E. McIntyre; Richard D. Stevens; Joseph D. Manthey; Carlos Portillo‐Quintero; Natasja Van Gestel; Sergio A. Balaguera‐Reina; Brandon A. Gross; Margaret Munn; Llewellyn D. Densmore (Journal of Biogeography, 2026)
Aim Phylogenetic niche conservatism, the tendency of closely related species to retain ancestral ecological traits, has gained considerable interest, yet the lack of integration across independent evaluation methods has hindered our understanding of whether niches are conserved or dynamic. Such an understanding is especially relevant for taxa of conservation concern, such as crocodylians (order Crocodylia). This study assessed niche conservatism among New World crocodylians by combining ensemble species distribution models, phylogenetics, and standard metrics of geographic and environmental niche overlap. Location America. Major Taxa Order Crocodylia. Methods We estimated species' climatic niches in geographic and environmental dimensions to assess overlap patterns and quantified associations between niche overlap and phylogenetic patristic distance using the Mantel test and phylogenetic independent contrast (PIC). Results Overlap analyses in geographic and environmental spaces revealed climatic niche differentiation across the clade, suggesting divergent environmental preferences among species. The relationship between phylogenetic patristic distance and climatic niche overlap assessed via Mantel tests revealed a significant negative correlation with geographic niche overlap ( ρ = −0.361, p = 0.005), but no evidence for associations with environmental niche overlap (Schoener's D: ρ = −0.079, p = 0.184; Hellinger's I: ρ = −0.063, p = 0.250), suggesting that more distantly related species overlap less geographically. In contrast, the relationship assessed using PIC revealed no evidence for associations between phylogenetic distance and either geographic ( ρ = −0.200, p = 0.579) or environmental niche overlap (D: ρ = −0.294, p = 0.41; I: ρ = −0.319, p = 0.369). Conclusions We found no strong or consistent evidence for phylogenetic conservatism in climatic niches across both geographic (inverse relationship) and environmental (no relationship) dimensions in New World crocodylians. This study enhances our understanding of niche dynamics and highlights the value of integrating niche modelling with phylogenetic analyses to detect biogeographic and evolutionary patterns.